1977
DOI: 10.1159/000250979
|View full text |Cite
|
Sign up to set email alerts
|

Histiocytosis X in an Adult with Skin and Uncommon Central Nervous System Involvement

Abstract: Report of a case of histiocytosis X with adult onset, widespread skin lesions and rare central nervous system involvement resulting in dizziness and ataxia. On autopsy histiocytosis X infiltrates in the central nervous system were demonstrated with granuloma formation in the temporal lobe and nucleus dentatus of the cerebellum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1979
1979
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Indeed, Haslam's case resembles our case; he describes a 20-year-old man with a progressive cerebellar ataxia, in whom diabetes insipidus and characteristic bone lesions, 10 years after ataxia onset, ultimately led to the diagnosis of LCH [9]. The pathological substrate for the cerebellar dysfunction in LCH seems to be a degenerative process reflected by cell loss (Purkinje cell layer and dentate nucleus), demyelination, gliosis, and atrophic changes, while active cellular infiltrates have been observed less frequently [1,10,12]. It is possible that primary histiocytic infiltration of the cerebellum and brainstem precedes 'secondary' degenerative neuronal damage.…”
supporting
confidence: 55%
“…Indeed, Haslam's case resembles our case; he describes a 20-year-old man with a progressive cerebellar ataxia, in whom diabetes insipidus and characteristic bone lesions, 10 years after ataxia onset, ultimately led to the diagnosis of LCH [9]. The pathological substrate for the cerebellar dysfunction in LCH seems to be a degenerative process reflected by cell loss (Purkinje cell layer and dentate nucleus), demyelination, gliosis, and atrophic changes, while active cellular infiltrates have been observed less frequently [1,10,12]. It is possible that primary histiocytic infiltration of the cerebellum and brainstem precedes 'secondary' degenerative neuronal damage.…”
supporting
confidence: 55%
“…Of particular fascination is that the patient developed the disease at such a great age. The author knows of only three earlier reports of Letterer-Siwe disease in elderly patients which included ultrastructural findings (Vollum & Farquharson, 1974;Benisch, Peison & Carter, 1977;Amirdjazil, Serban-Aurel & Konrad, 1977). AH described the typical and now welt recognized features ofthe invading HX cells sueh as the lobulated and indented nuclei, and specific cytoplasmic granules (Langerhans' cell granules).…”
Section: Discussionmentioning
confidence: 99%
“…Initially, generalized histiocytosis X appeared to be confined to infants and children (Abt and Denenholz 1936). Subsequently the disease has also been reported in adults (Enriquez et al 1967;Feuerman and Sandbank 1976;Amirdjazil, Esca and Konrad 1977;Nethercott et al 1983) although the number of reported cases remains small.…”
Section: Introductionmentioning
confidence: 96%